Implementasi Algoritma C5.0 pada Penilaian Kinerja Pegawai Negeri Sipil - Kastawan, Putu Wirya; Wiharta, Dewa Made; Sudarma, Made (Majalah Ilmiah Teknologi Elektro, 2018)
Employees become the spearhead of every Company, whether it is run the business on manufacture or service. The position and role of public government employees as an element of civil servant obligate them to provide fair public services. Refers to those facts, the performance of public government employees needs to be well managed. The algorithm C5.0 is one of the decision tree algorithm which can process the employees performance data become an input for decision-making. Based on evaluation result of 184 employees performance datas, there was a high accurracy data in level 96.08%. Due to  that result, the algorithm system can be developed become e-performance system which can predict or giving an advice in order to decision-making processes whether for assigning promotion, ranking or giving performance allowances.